Understanding healthcare workers’ knowledge and attitudes regarding the coronavirus disease 2019 (COVID-19) vaccine: Overcoming gaps to improve public health response - James Mo; Catherine J. Maples; Amanda Harris; Monica P. Meyer; Teena Chopra (Antimicrobial Stewardship & Healthcare Epidemiology, 2022)
Vaccines serve as a major tool against the coronavirus disease 2019 (COVID-19) pandemic, but vaccine hesitancy remains a major concern in the United States. Healthcare workers (HCWs) strongly influence a patient’s decision to get vaccinated. We evaluated HCW knowledge and attitudes regarding the COVID-19 vaccine.